Logistics input complexity and comparative advantage in manufacturing: Based on the perspective of global value chains - Lei Yang; Dong Qianli; Ziqiang Tong; Jiani Wu; Hua Yao (Journal of Applied Economics, 2024)
Logistics is an essential service for manufacturing because it supports the coordination and integration of global production activities, ultimately reducing costs and improving efficiency. However, it is not clear that the complex structural relationship between logistics and manufacturing under the Global Value chains (GVCs). Consequently, employing the input-output model, we develop the logistics input complexity (LIC) to capture the complex structural characteristics of logistics services embodied in manufacturing sectors and investigate its role in manufacturing comparative advantage. We find that the logistics input complexity can boost manufacturing competitiveness. Furthermore, we also confirm that the domestic and foreign groups of LIC have at least a partially complementary effect on the export competitiveness of manufacturing. Finally, we identify heterogeneity in the domestic and foreign groups' five subdivision logistics modes of LIC. It suggests that logistics service providers must precisely match the related manufacturing production chains to cultivate a comparative advantage in manufacturing.
Keywords: 330; comparative advantage; Global value chains; logistics input complexity; manufacturing